Reproductive health issues in rural Western Kenya - Ouma Peter; Ayisi John G; Sikuku Evallyne; Peterson Elizabeth; Odhiambo Frank; Lindblade Kim A; van Eijk Anna M; Rosen Daniel H; Slutsker Laurence (BMC, 2008)
Abstract Background We describe reproductive health issues among pregnant women in a rural area of Kenya with a high coverage of insecticide treated nets (ITNs) and high prevalence of HIV (15%). Methods We conducted a community-based cross-sectional survey among rural pregnant women in western Kenya. A medical, obstetric and reproductive history was obtained. Blood was obtained for a malaria smear and haemoglobin level, and stool was examined for geohelminths. Height and weight were measured. Results Of 673 participants, 87% were multigravidae and 50% were in their third trimester; 41% had started antenatal clinic visits at the time of interview and 69% reported ITN-use. Malaria parasitemia and anaemia (haemoglobin < 11 g/dl) were detected among 36% and 53% of the women, respectively. Geohelminth infections were detected among 76% of the 390 women who gave a stool sample. Twenty percent of women were underweight, and sixteen percent reported symptoms of herpes zoster or oral thrush in the last two months. Nineteen percent of all women reported using a contraceptive method to delay or prevent pregnancy before the current pregnancy (injection 10%, pill 8%, condom 0.4%). Twenty-three percent of multigravidae conceived their current pregnancy within a year of the previous pregnancy. More than half of the multigravidae (55%) had ever lost a live born child and 21% had lost their last singleton live born child at the time of interview. Conclusion In this rural area with a high HIV prevalence, the reported use of condoms before pregnancy was extremely low. Pregnancy health was not optimal with a high prevalence of malaria, geohelminth infections, anaemia and underweight. Chances of losing a child after birth were high. Multiple interventions are needed to improve reproductive health in this area.